Structural Synthesis of Uncertain Joints in the Drawings of Tain Gong Kai Wu - HSIAO, Kuo-Hung; YAN, Hong-Sen (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2010)
This work presents an approach for structural synthesis of ancient drawings which are illustrated uncleanly and with uncertain joints. Based on the structural analysis of the mechanism, the characteristics and design constrains of the drawings with uncertain joints are concluded. Then, according to the concepts of generalization and specialization subject to the concluded design constrains, all feasible structures of mechanism are reconstructed that meet the technological standards of the subjects’ time period. Three examples in book Tain Gong Kai Wu are provided to illustrate the proposed approach. And, this provides a logical foundation to deal with the issue for the ancient drawings with uncertain joints.